THE ROLE OF TEACHERS IN INSTILLING ISLAMIC VALUES OF STUDENTS IN FULL-DAY SCHOOL-BASED ELEMENTARY SCHOOLS AND ISLAMIC BOARDING SCHOOLS SYSTEM - Nahdiyah, Atika Cahya Fajriyati; Chairy, Ach; Najib, Muhammad; Fajriati, Nita; Putro, Khamim Zarkasih (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The purpose of this study was to determine the teacher's role in instilling Islamic values in students in full day school and Islamic boarding school based elementary schools. This study uses a qualitative method with a descriptive approach. Data collection techniques in the form of observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion. The results of this study are that the teacher plays an important role in instilling Islamic values in students because a teacher is assigned to not only teach and provide values but is also responsible for forming the noble character of students so that they have personalities and behaviors that are in accordance with Islamic values. Instilling Islamic values of students in Full Day School-Based Elementary Schools & Islamic Boarding School Systems, namely SD Al-Qur'an Minhajuth Thullab Pekalongan, East Lampung Regency through religious activities including: habituation in midday and afternoon prayers in congregation, dhuha prayer, habituation through typical pesantren curriculum programs, faith and piety building nights, and so on.